1979
DOI: 10.1520/jfs10849j
|View full text |Cite
|
Sign up to set email alerts
|

Particle Analysis for the Detection of Gunshot Residue. II: Occupational and Environmental Particles

Abstract: The first paper in this series [1] described the application of particle analysis to the identification of gunshot residue. In the course of developing this application, gunshot residue was identified in each of several hundred samples collected. In many instances, the nonfiring hand was sampled as a control, or “handblank” samples were taken from persons who had not fired a gun [2]. Some of these many tests were performed “blind,” that is, without prior knowledge by the analyst of the nature of the sample. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 2 publications
2
56
0
Order By: Relevance
“…PIXE detects small quantities of a number of different elements (including Sn, Al, Si, Cl, Ca, and Zn) that are not detected by SEM-EDS. It is known from previous studies that certain gunshot residues can contain these elements [2]. In agreement with the SEM-EDS measurement, the measured K content of the pistol residue is higher than for the shotgun residue.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…PIXE detects small quantities of a number of different elements (including Sn, Al, Si, Cl, Ca, and Zn) that are not detected by SEM-EDS. It is known from previous studies that certain gunshot residues can contain these elements [2]. In agreement with the SEM-EDS measurement, the measured K content of the pistol residue is higher than for the shotgun residue.…”
Section: Resultssupporting
confidence: 88%
“…The particles are made up of material from the primer, bullet, bullet jacket, cartridge casing and the gun barrel, are spherical, and are of the order of a few microns in diameter. There are several types of particle that are characteristic of gunshot residue, including those containing Pb, Ba and Sb [2]. …”
mentioning
confidence: 99%
“…With respect to this, studies have confirmed that, in the majority of cases, people with automobile-related jobs such as mechanics (batteries, motors, tyres), automotive electricians, users of cartridge-operated industrial tools, and people who work with fireworks have been shown to have higher levels of Ba, Pb and Sb on their hands, which, in some cases, may cause "false-positive" results. 2,3,7,8 For criminal justice, however, evidence of gunshot residue is only taken into consideration when "unique" GSR particles with the following elemental compositions: (1) Pb-Ba-Sb, (2) Sb-Ba or (3) Pb-Ba-Ca-Si-Sn are found.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to this, studies have confirmed that, in the majority of cases, people with automobile-related jobs such as mechanics (batteries, motors, tyres), automotive electricians, users of cartridge-operated industrial tools, and people who work with fireworks have been shown to have higher levels of Ba, Pb and Sb on their hands, which, in some cases, may cause "false-positive" results. 2,3,7,8 For criminal justice, however, evidence of gunshot residue is only taken into consideration when "unique" GSR particles with the following elemental compositions: (1) Pb-Ba-Sb, (2) Sb-Ba or (3) Pb-Ba-Ca-Si-Sn are found.Chemical tests, based on color reactions to identify suspects at crime scenes, such as the "dermal nitrate test", 9 Griess reagent 10 and sodium rhodizonate, 11 but due to numerous incidences of false positive results these tests were abandoned by forensic scientists. Nowadays, the investigation of gunshot residue particles in forensic laboratories is usually performed by scanning electron microscopy-energy-dispersive X-ray spectroscopy (SEM-EDS), 12,13 using the tape-lift method for sample collection.…”
mentioning
confidence: 99%
“…1 Based on SEM C EDS analysis, particles are classified 2,3 as 'unique' GSR or 'consistent' with GSR nature. For particles of the former type, SEM C EDS represents an exhaustive means to ensure their classification.…”
Section: Introductionmentioning
confidence: 99%